2015
DOI: 10.1007/s12311-015-0746-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Contribution to Social Cognition

Abstract: Emotion attribution (EA) from faces is key to social cognition, and deficits in perception of emotions from faces underlie neuropsychiatric disorders in which cerebellar pathology is reported. Here we test the hypothesis that the cerebellum contributes to social cognition through EA from faces. We examined fifty-seven patients with cerebellar disorders and 57 healthy controls. Thirty-one patients had complex cerebrocerebellar disease (CD); 26 had disease isolated to cerebellum (ID). EA was measured with the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 100 publications
(130 reference statements)
17
109
0
Order By: Relevance
“…Despite the extensive amount of literature on the involvement of cerebellum in psychiatric disorders [18][19][20][21][22][23], studies on the involvement of the cerebellum in PSD are scarce. In the present study, we applied multi-modality MRI and 1H-MRS to study morphology and metabolism of cerebellum and found morphological and metabolic alteration of the cerebellum in the PSD patients and the extent of those alterations are positively correlated with the severity of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the extensive amount of literature on the involvement of cerebellum in psychiatric disorders [18][19][20][21][22][23], studies on the involvement of the cerebellum in PSD are scarce. In the present study, we applied multi-modality MRI and 1H-MRS to study morphology and metabolism of cerebellum and found morphological and metabolic alteration of the cerebellum in the PSD patients and the extent of those alterations are positively correlated with the severity of depression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies have found that schizophrenia ,depression and other mental disorders were associated with cerebellar lesions [19][20][21][22], cerebellum lesions could cause cognitive emotional disorders [23] and reduction of the cerebellum volume was positively correlated with the severity of the depression [11,24]. On the other hand, in our previous study, we showed that electroacupuncture at the GB12 acupoint (corresponding to cerebellar fastigial nucleus) improved the behavior of PSD rats [25], such finding was also implicated in patients with PSD [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have focused on the performance of patients with cerebellar dysfunction on tests of social cognition, nor have non-invasive brain stimulation studies in healthy individuals been conducted to test specific causal hypotheses. Impaired performance on Theory of Mind (ToM) tasks has been recently reported in heterogeneous patient groups with cerebellar damage, including stroke, atrophy and spinocerebellar ataxia (SCA) [109111]. Most ToM tests require attribution of mental states, beliefs and intentions to others on the basis of short stories, animations or eye expressions.…”
Section: The Cerebellum In Social Cognition and Affective Processingmentioning
confidence: 99%
“…A patient with massive bilateral ponto-cerebellar ischemia was impaired on the Reading the Mind in the Eyes Test (RMET), along with other ToM deficits (Roldan Gerschcovich et al, 2011). A larger scale study on 57 patients with various types of cerebellar damage (degeneration, hemorrhage, ischemia, and tumors; confined to the cerebellum in 26 patients) reported deficient performance on the RMET and impaired emotional regulation (Hoche et al, 2016).…”
Section: Socio-cognitive Deficits In Patients With Focal Cerebellar Lmentioning
confidence: 99%